Seven brief lessons on physics eaudiobook - Rovelli, Carlo (Penguin Audio, 2016)
The New York Times bestseller from the author of The Order of Time and Reality Is Not What It Seems , Helgoland , and Anaximander “One of the year’s most entrancing books about science.” —The Wall Street Journal “Clear, elegant...a whirlwind tour of some of the biggest ideas in physics.” — The New York Times Book Review   This playful, entertaining, and mind-bending introduction to modern physics briskly explains Einstein's general relativity, quantum mechanics, elementary particles, gravity, black holes, the complex architecture of the universe, and the role humans play in this weird and wonderful world. Carlo Rovelli, a renowned theoretical physicist, is a delightfully poetic and philosophical scientific guide. He takes us to the frontiers of our knowledge: to the most minute reaches of the fabric of space, back to the origins of the cosmos, and into the workings of our minds. The book celebrates the joy of discovery.  “Here, on the edge of what we know, in contact with the ocean of the unknown, shines the mystery and the beauty of the world,” Rovelli writes. “And it’s breathtaking.”